Prevalence Study on Feline Trypanosomiasis in and Around Hyderabad, India - , Dhileep K, Padmaja K, Lakshmi K (Archives of Current Research International, 2025)
Aim:To determine the prevalence of Trypanosomiasis in cats in and around Hyderabad, and to study the associated clinical signs and therapeutic management. Study Design: The study involved cats presented to the Veterinary Clinical Complex (VCC), College of Veterinary Science, Rajendra Nagar, Hyderabad, as well as those referred from local dispensaries with clinical signs suggestive of Trypanosomiasis, such as fever and unilateral or bilateral corneal opacity. Data were analyzed based on breed, age, and gender. Place and Duration of Study: The study was conducted at the VCC, College of Veterinary Science, Rajendra Nagar, Hyderabad, from September 2024 to March 2025. Methodology: Suspected cases were screened for Trypanosomiasis using wet blood film examination, Giemsa stained blood smears along with hematological and biochemical analyses. The data obtained was subjected to statistical analysis. Results: Out of 1002 cats examined, 16 (1.6%) were diagnosed with Trypanosomiasis. The majority of affected cats were Domestic Short Hair (DSH) breed (62.5%), and young males (less than 1 year of age) were predominantly affected. The most common clinical signs included corneal opacity (87.5%), fever (81.25%), lymphadenopathy (75%), Inappetence (56.25%), pale mucous membranes (50%), turbidity in the anterior chamber (43.75%) and dehydration (31.25%). Microscopic examination of wet blood films revealed motile, spindle-shaped trypomastigote forms of Trypanosoma spp., which were also confirmed in Giemsa-stained blood smears. Hematological and biochemical findings included anemia, eosinophilia, and hypoglycemia. Treatment and Outcome: Affected cats were treated with Diminazene aceturate at a dosage of 3.5 mg/kg body weight for five consecutive days, along with supportive symptomatic therapy. All treated cats showed complete clinical recovery following the full course of treatment. Conclusion: Trypanosoma spp were detected in some cats presented at VCC College of Veterinary Science, Rajendranagar, Hyderabad.In cats, unlike in dogs, Diminazene aceturate must be administered for five consecutive days to achieve complete recovery. Interruption of the treatment regimen may lead to relapse.